Radiation curable compositions for composites

By developing a composite material composition containing ethylenically unsaturated parts and cycloaliphatic structures, the problems of long cycle time and excellent materials in the existing composite material manufacturing technology are solved, and high-efficiency and low-cost mass production is achieved. And provides flexibility and high heat resistance.

CN119487108APending Publication Date: 2025-02-18ALLNEX BELGIUM SA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380050793.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-02-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing composite material manufacturing technology is cost-effective due to long heating and cooling cycle times and is difficult to use in large-scale applications. At the same time, the existing UV-curable compositions are hard after curing, making it difficult to meet the flexibility requirements of certain applications.

Method used

An actinic radiation and/or thermally curable composition was developed, containing at least 20% by weight of Compound A and Compound B, respectively, containing ethylenically unsaturated moieties and cycloaliphatic structures, combined with low viscosity Compound C, to ensure that The composition has a high glass transition temperature and good elongation after curing.

Benefits of technology

The composition can be used in high-speed production conditions for large-scale applications, providing flexibility and high heat resistance, and almost no shrinkage during curing, avoiding warping and poor fit problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216740990000141
    Figure BDA0005216740990000141
  • Figure BDA0005216740990000151
    Figure BDA0005216740990000151
  • Figure BDA0005216740990000161
    Figure BDA0005216740990000161
Patent Text Reader

Abstract

An actinic radiation curable and / or heat curable composition (I) for composite materials comprising: (A) at least 20 wt% of a compound A comprising at least 2 ethylenically unsaturated moieties and a structural moiety; (B) at least 20 wt% of a compound B comprising at least 2 ethylenically unsaturated moieties and an alicyclic or heterocyclic aliphatic structure; (C) 1-40 wt% of a compound C different from compounds A and B, comprising substantially one ethylenically unsaturated moiety and having a viscosity of less than 100 mPa.s, preferably less than 50 mPa.s, even more preferably less than 25 mPa.s, determined at 25 DEG C; and (D) 0-20 wt% of a compound D different from compounds A, B and C, comprising at least one ethylenically unsaturated moiety; wherein the total content of compounds B and A is 60-99 wt% with respect to the total content of compounds A, B, C and optionally D.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to actinic radiation and / or thermally curable compositions for composite materials, composite materials comprising such compositions and filler materials, and methods of applying said filler materials. Background Art

[0002] Composite materials are a combination of two or more immiscible materials, usually including a plastic or resin matrix and a filler material, where the resin holds the filler together and forms a continuous phase to bond the structure and filler material. Composite materials can have various shapes and mechanical properties depending on the application. Composite materials are used in a wide range of applications, for example in automotive, aerospace, transportation, construction, electronics. Composite materials are often used to make pipes, such as geothermal pipes, and are also used to make pipes for offshore and onshore applications.

[0003] Prior art composite material manufacturing techniques are generally less cost effective due to the long curing process via heating and cooling cycle times. This prevents them from being used in high volume applications. The use of radiation curing in composite material manufacturing can significantly reduce this cycle time, as the curing process is very rapid and is carried out at low temperatures. This makes it suitable for mass production of composite materials. UV light curable compositions have been developed that can form a resin matrix for filler materials. The advantage of UV light is that the curing speed is very fast, thereby significantly enhancing the manufacturing process.

[0004] WO 2014 / 191308 A1 describes UV light-curable compositions, wherein the composite composition comprises a resin containing isosorbide diacrylate. Compositions of this type have the disadvantage that the composite materials they provide are relatively hard once cured.

[0005] Many applications require composite materials to have a certain degree of flexibility, while also having to withstand a certain amount of stress and have a certain degree of toughness. It is difficult to achieve a good balance between these properties. SUMMARY OF THE INVENTION

[0007] The inventors have now surprisingly found a composition which at least partially overcomes the above problems by providing an actinic radiation and / or thermally curable composition (I) as claimed in claim 1. Therefore, a first aspect of the present invention relates to an actinic radiation and / or thermally curable composition for composite materials, comprising:

[0008] (A) at least 20 wt% of a compound A comprising at least 2 ethylenically unsaturated moieties and a moiety selected from the group consisting of polyalkylene glycols (e.g. polyethylene glycol, polypropylene glycol), polycaprolactone, polybutadiene or a hydrogenated or partially hydrogenated form thereof, polyisoprene or a hydrogenated or partially hydrogenated form thereof, polyesters derivable from polyols and dicarboxylic acids;

[0009] (B) at least 20 wt% of a compound B comprising at least 2 ethylenically unsaturated moieties and a cycloaliphatic structure or a heterocycloaliphatic structure;

[0010] (C) 1 to 40 wt% of a compound C different from compounds A and B, which contains essentially one ethylenically unsaturated part and has a viscosity measured at 25° C. of less than 100 mPa.s, preferably less than 50 mPa.s, even more preferably less than 25 mPa.s;

[0011] (D) 0-20 wt% of a compound D different from compounds A, B and C, which contains at least one ethylenically unsaturated moiety;

[0012] wherein the total content of compounds B and A is 60-99 wt % relative to the total content of compounds A, B, C and optionally D; and

[0013] Wherein composition (I) has a glass transition temperature (Tg) of at least 90°C after curing, as determined using dynamic mechanical analysis according to standard test method ASTM E1640.

[0014] It has been found that such compositions can be used in composite materials and have one or more of the following advantages:

[0015] ●They can be suitable for high-volume applications with high-speed production;

[0016] ●They can be used to form a wide variety of composite products;

[0017] • They may be suitable for obtaining composite articles while undergoing little shrinkage upon curing, thereby preventing warping and / or poor fit of parts;

[0018] ●They can have low toxicity;

[0019] ●They can be BPA-free;

[0020] ●They can be styrene-free;

[0021] ● Composition (I) may have a low viscosity, thereby facilitating its use in liquid composite manufacturing processes;

[0022] ● Composition (I) can have a good pot life even at room temperature;

[0023] • The storage cost of composition (I) is low.

[0024] In addition, it has been found that such compositions provide composite materials with a certain flexibility and still high heat resistance after actinic radiation and / or thermal curing, which means that the composition provides a coating with a sufficiently high glass transition temperature and good elongation properties and can withstand high ultimate bending strains. Compositions with high Tg are usually hard and brittle. It has been surprisingly found that the compositions of the present invention can be flexible after curing while still having a high Tg. In some cases, they even have good salt water resistance.

[0025] Therefore, the present invention also relates to a second aspect, a composite material comprising the curable composition (I) of the first aspect and a filler material (II).

[0026] In a third aspect, the present invention relates to a method for manufacturing a composite material, comprising the steps of:

[0027] · contacting a filler material with the curable composition (I) of the first aspect;

[0028] • Curing the curable composition (I) in contact with the filler material.

[0029] This may provide one or more of the following advantages:

[0030] It can be fast;

[0031] It can be carried out at low temperature;

[0032] It can be processed as needed, thus facilitating processing in industrial production;

[0033] It can be cost-effective;

[0034] It can be used for high volume applications;

[0035] It can require low energy consumption, in part because no heating is required. DETAILED DESCRIPTION OF THE INVENTION

[0037] A first aspect relates to an actinic radiation and / or thermally curable composition (I) for composite materials, comprising:

[0038] (A) at least 20 wt% of a compound A comprising at least 2 ethylenically unsaturated moieties and a moiety selected from the group consisting of polyalkylene glycols, polycaprolactones, polybutadiene or hydrogenated or partially hydrogenated forms thereof, polyisoprene or hydrogenated or partially hydrogenated forms thereof, polyesters derivable from polyols and dicarboxylic acids;

[0039] (B) at least 20 wt% of a compound B comprising at least 2 ethylenically unsaturated moieties and a cycloaliphatic structure or a heterocycloaliphatic structure;

[0040] (C) 1 to 40 wt% of a compound C different from compounds A and B, which contains essentially one ethylenically unsaturated portion and has a viscosity measured at 25° C. of less than 100 mPa.s, preferably less than 50 mPa.s, even more preferably less than 25 mPa.s;

[0041] (D) 0-20 wt% of a compound D different from compounds A, B and C, which contains at least one ethylenically unsaturated moiety;

[0042] wherein the total content of compounds B and A is 60-99 wt % relative to the total content of compounds A, B, C and optionally D; and

[0043] Wherein composition (I) has a glass transition temperature (Tg) of at least 90°C after curing, as determined using dynamic mechanical analysis according to standard test method ASTM E1640.

[0044] It has been found that such a composition can provide a material having an ultimate tensile elongation of greater than 3%, preferably greater than 5%, after curing, wherein the tensile elongation is determined according to ASTM D638, a standard test method for determining uniaxial stress-strain (tensile) properties. Such a composition is suitable for composite materials requiring a certain formability, for example for (windable) pipes, (printed) sleeves and windmill blades. The composition (I) of the first aspect can also be used for repairing articles made of composite materials.

[0045] The composition (I) has a glass transition temperature after curing of not less than 90° C., preferably not less than 100° C., wherein Tg is determined according to standard test method ASTM E1640 using dynamic mechanical analysis.

[0046] It has also been found that such a composition provides, after curing, a material having very high plastic flexural properties and having an ultimate flexural strain greater than 5%, preferably greater than 6%, as determined by a three-point bending test according to standard test method ASTM D790.

[0047] Thus, in one embodiment, the curable composition (I) has an ultimate tensile elongation greater than 3% and an ultimate flexural strain greater than 5%.

[0048] As used herein, "ethylenically unsaturated moiety" refers to a moiety comprising polymerizable ethylenically unsaturated groups. "Polymerizable ethylenically unsaturated groups" refer to carbon-carbon double bonds that can undergo free radical polymerization under the influence of an initiator and / or radiation, ultimately in the presence of a photoinitiator. The polymerizable ethylenically unsaturated groups are typically selected from (meth)acrylic groups. In the present invention, the term "(meth)acrylic" is understood to cover acrylic and methacrylic groups present on the compound, either alone or in the form of a mixture thereof.

[0049] As used herein, "actinic radiation curable composition" refers to a composition that can be at least partially cured by electromagnetic radiation (e.g. near infrared light, visible light, UV light or X-rays, in particular UV light) or microparticle radiation (e.g. electron beam). Actinic radiation can occur in the presence of a photoinitiator (system). Preferably, the composition of the first aspect is fully cured after exposure to actinic radiation.

[0050] As used herein, "composite material" refers to a composite material composed of a plastic matrix or a resin matrix, wherein the resin matrix holds reinforcing components together. The reinforcing components in the composite material will increase the stiffness and tensile strength of the composite material.

[0051] UV light radiation refers to irradiation by ultraviolet light sources and LED light sources, and the ultraviolet light sources include high-pressure or low-pressure mercury lamps, cold cathode tubes, xenon lamps, black light lamps, ultraviolet lasers and flash lamps. Typically, the wavelength of the UV light source is between 240-405nm.

[0052] Irradiation using an LED light source refers to illumination by a light emitting diode source, wherein a semiconductor light source is used. Typically, a wavelength of 365, 385, 395 or 405 nm is used.

[0053] As used herein, "heat-curable compositions" are compositions that can be cured by polymerization initiated by free radical generators (including peroxides and azo initiators). Peroxide initiators include diacyl peroxides, hydroperoxides, ketone peroxides, peroxyesters, peroxyketals, dialkyl peroxides, alkyl peresters, and percarbonates, etc., used alone or in conjunction with a redox system. Examples of these peroxides include methyl ethyl ketone peroxide (MEKP), methyl isobutyl ketone peroxide (MIBK), benzoyl peroxide (BPO), and cumene hydroperoxide (CHP). Combinations of two or more peroxides can be used to cure the resin. Azo initiators include azobisisobutyronitrile (AIBN) and related compounds thereof.

[0054] The free radical reaction can be accelerated by using metal carboxylates (e.g., cobalt naphthenate and cobalt octoate). Zinc, iron, vanadium, potassium and other metal complexes can also be used in the process. Nitrogen-containing compounds (e.g., derivatives of aniline, various amides, aromatic and aliphatic amines) can be used to enhance the curing. In the absence of such accelerators, curing can be carried out by heating to a temperature, for example, higher than 60° C. When an accelerator is present, curing can be carried out at room temperature (i.e., about 20° C.), or by heating at a higher temperature (e.g., 30° C. or higher).

[0055] "For use in composite materials" means "suitable for use in composite materials".

[0056] Compound A comprises at least 2 ethylenically unsaturated moieties and a moiety selected from polyalkylene glycols, polycaprolactones, polybutadiene or hydrogenated or partially hydrogenated forms thereof, polyisoprene or hydrogenated or partially hydrogenated forms thereof, or polyesters derivable from polyols and dicarboxylic acids.

[0057] In one embodiment, the moiety is derived from a compound having a Tg below 0°C, preferably below -20°C, more preferably below -30°C, even more preferably below -40°C.

[0058] Preferably, upon homopolymerization, compound A has a Tg greater than 0° C., more preferably greater than 10° C., even more preferably greater than 30° C. Preferably, the Tg is lower than 80° C.

[0059] In one embodiment, the polyester moiety may be derived from:

[0060] ● condensation reaction of a straight-chain aliphatic dicarboxylic acid having 4 to 14 carbon atoms with an aliphatic or alicyclic polyol (preferably an aliphatic diol or an alicyclic diol),

[0061] ● condensation reaction of dimerized fatty acid compounds with aliphatic or alicyclic diols, or

[0062] ●Condensation reaction of dimerized fatty alcohol compounds with aliphatic diacid compounds.

[0063] The polyalkylene glycol moiety preferably has the structure -((CH2) n O) x -or-(CH2CH(CH3)O) x -, wherein n is an integer from 2 to 5, and x is an integer from 5 to 20. Preferred examples are the following moieties: polyethylene glycol (Tg is about -67°C), bio-based polypropylene glycol (also known as poly(trimethylene glycol) or poly(1,3-propylene glycol), Tg is about -77°C), polypropylene glycol (Tg is about -74°C), polytetrahydrofuran (also known as polytetramethylene oxide, Tg is about -86°C).

[0064] The polycaprolactone moiety preferably has the structure -(C(C=O)(CH2) u O) t -, wherein u is an integer from 3 to 5 and t is an integer from 4 to 20. Typically, the moiety is derived from a polycaprolactone having a Tg of about -66°C.

[0065] The polybutadiene moiety preferably has the structure -(CH2-CH(CH=CH2) p -(CH2-CH=CH-CH2) q-, wherein the sum of p and q is an integer from 10 to 100, and wherein p≥0, q≥0; or a hydrogenated or partially hydrogenated form thereof. Preferred examples are the following moieties: poly(1,2-butadiene) (Tg is about -13°C) and poly(1,4-butadiene) (Tg is about -105°C).

[0066] The polyisoprene moiety preferably has the structure -(CH2-C(CH3)=CH-CH2) r -, wherein r is an integer of 10 to 100, or a hydrogenated or partially hydrogenated form thereof.

[0067] The polyester moiety preferably has the structure -(O(C=O)-R'-(C=O)OR"-) n -,in:

[0068] R' is a saturated straight chain alkyl group having 2 to 14 carbon atoms, R" is a saturated aliphatic or alicyclic alkyl group, and n is an integer of 3 to 20;

[0069] R' is a dimeric fatty acid residue, R" is a saturated aliphatic or alicyclic alkyl group, and n is an integer from 3 to 20;

[0070] R' is an aliphatic diacid residue, R" is a dimerized fatty diol residue, and n is an integer of 3-20.

[0071] Examples of polyester moieties where R' is a saturated linear alkyl group having 4 to 14 carbon atoms and R" is a saturated aliphatic or alicyclic alkyl group are those derived from poly(ethylene glycol adipate) (Tg of about -44°C), poly(1,4-butylene glycol adipate) (Tg of about -68°C).

[0072] Examples of polyester moieties wherein R' is a dimerized fatty acid residue, R" is a saturated aliphatic or alicyclic alkyl group and n is an integer from 3 to 20 or wherein R' is an aliphatic diacid residue, R" is a dimerized fatty diol residue and n is an integer from 3 to 20 are Pripol, commercially available from Croda. TM or Priplaster TM Series of polyester.

[0073] Compound A is present in an amount of at least 20 wt % relative to the total amount of composition (I) comprising compounds A, B, C and optionally compound D.

[0074] Preferably, compound A comprises at least 2 (meth)acrylate groups and at most 8, more preferably at most 6 (meth)acrylate groups.

[0075] In one embodiment, the weight average molecular weight of the structural part is 200-10000, more preferably 400-5000.

[0076] In a preferred embodiment, compound A is a polyester di- or tri-(meth)acrylate or a polyurethane di- or tri-(meth)acrylate, wherein the polyester (meth)acrylate is a reaction product of (meth)acrylic acid with a polyol comprising a moiety as defined above, and the polyurethane (meth)acrylate is a reaction product of a mono- or poly-hydroxy (meth)acrylate, a mono- or poly-isocyanate with a compound comprising a moiety as defined above. A person skilled in the art is able to prepare such polyesters or polyurethanes.

[0077] Preferred examples of compound A are di- or tri-(meth)acrylate compounds containing a structural moiety based on a poly(butylene oxide), poly(propylene oxide), poly(ethylene oxide) moiety, a polyester moiety formed as a condensation reaction product of a C4-C20 straight-chain alkyl diacid and an aliphatic or alicyclic diol compound, a polyester moiety formed by a condensation reaction of a dimerized fatty acid and an aliphatic or alicyclic diol, or a polyester moiety formed by a condensation reaction of a dimerized fatty diol and an aliphatic diacid compound.

[0078] Examples of such compounds include polyurethane di- or tri-(meth)acrylate compounds or polyester di- or tri-(meth)acrylate compounds containing these structural moieties.

[0079] Compound B comprises at least 2 ethylenically unsaturated moieties, preferably (meth)acrylate groups, and a cycloaliphatic structure or a heterocycloaliphatic structure.

[0080] In a preferred embodiment, compound B does not contain a structural part of compound A.

[0081] Compound B comprises at least 2 ethylenically unsaturated moieties and preferably no more than 8, more preferably no more than 6 ethylenically unsaturated moieties.

[0082] Compound B also has a cyclic structure, and the cyclic structure is a cycloaliphatic structure of a heterocyclic aliphatic structure. The structure can also be polycyclic. "Cycloaliphatic structure" refers to an aliphatic hydrocarbon containing at least one cyclic structure. "Heterocyclic aliphatic structure" refers to a cyclic structure having atoms of at least two different elements as its ring members. The atoms are preferably carbon, amine, oxygen and / or sulfur. The olefinic unsaturated part of compound B can be connected to the cyclic structure, or a connecting group can be present between the olefinic unsaturated part and the cyclic structure. The cyclic structure can have other functional groups. Compound B does not contain an aromatic ring structure.

[0083] Preferred examples of compound B are tricyclodecane dimethanol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, isosorbide-based poly(meth)acrylate (e.g. isosorbide di(meth)acrylate), tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate.

[0084] The composition (I) comprises at least 20 wt% of compound A, preferably 20-79 wt%, more preferably 20-40 wt%.

[0085] The composition (I) comprises at least 20 wt% of compound B, preferably 20-79 wt%, more preferably 20-50 wt%.

[0086] The total content of compounds B and A is 60-99 wt % relative to the total content of compounds A, B, C and optionally D.

[0087] Composition (I) also comprises 1-40 wt% of a compound C different from compounds A and B, said compound C containing essentially one ethylenically unsaturated part and having a viscosity measured at 25°C lower than 100 mPa.s, preferably lower than 50 mPa.s, even more preferably lower than 25 mPa.s.

[0088] Preferably, the substantially one ethylenically unsaturated part is a (meth)acrylate functional group. Preferably, the amount of compound C added to the composition (I) is such that the viscosity of the composition (I) measured at 25°C is equal to or less than 2500, preferably less than 1800, more preferably less than 1500, preferably less than 1000 mPa.s. The viscosity measured at 25°C is preferably above 100 mPa.s, more preferably above 200 mPa.s. Low viscosity is conducive to contact with filler materials. The application temperature (i.e., the temperature at which the composition (I) is contacted with the filler material to obtain a composite material) can be room temperature or a higher temperature.

[0089] Therefore, in one embodiment, the viscosity of the curable composition (I) measured at 25°C is equal to or less than 2500, preferably less than 1800, more preferably less than 1500 mPa.s.

[0090] Mono(meth)acrylate-functional compounds (C) having low viscosity are well known in the art. They contain essentially one radiation-curable (meth)acrylate group.

[0091] The mono(meth)acrylate functional compound (C) is a monofunctional (meth)acrylate monomer. Preferably, the number average molecular weight (Mn) of the (meth)acrylate functional monomer compound C used is on average 100-1000 Daltons, more preferably 120-800 Daltons, most preferably 120-500 Daltons. Typically, the weight average molecular weight (MW) is at most 1000 Daltons.

[0092] Preferably, upon homopolymerization, the mono(meth)acrylate functional compound (C) has a Tg of at least 40°C, more preferably greater than 50°C, even more preferably greater than 60°C.

[0093] Examples of suitable mono(meth)acrylate functional monomers are those of the formula CH2=C(R 1 )COOC z H 2z+1 Alkyl (meth) acrylate represented by 1 is a hydrogen atom or a methyl group, z is 1, wherein C z H 2z+1It may have a linear structure or a branched structure. Suitable examples of suitable mono(meth)acrylate functional monomers include, but are not limited to, β-carboxyethyl(meth)acrylate, methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, tert-butyl(meth)acrylate, pentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, octyl(meth)acrylate, octyldecyl(meth)acrylate, lauryl(meth)acrylate, cyclohexyl(meth)acrylate, phenoxyethyl(meth)acrylate, phenoxytetraethylene glycol(meth)acrylate, phenoxyhexaethylene glycol(meth)acrylate, phenoxy(meth)acrylate, 2-ethylhexyl(meth)acrylate, isopropyl glycol(meth)acrylate, isobornyl(meth)acrylate (IBO(M)A), 2-hydroxyethyl(meth)acrylate, hydroxypropyl(meth)acrylate, 4-hydroxy The invention also includes but is not limited to butyl (meth)acrylate, isobornyl (meth)acrylate, (meth)acryloyl morpholine, phenyl glycidyl ether (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, n-butylacryloyloxyethyl carbamate, glycerol (meth)acrylate, glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, the reaction products of (meth)acrylic acid with glycidyl esters of aliphatic carboxylic acids (e.g., neodecanoic acid) and mixtures thereof, styrene, norbornyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, allyl (meth)acrylate, benzyl (meth)acrylate, glycidyl (meth)acrylate and phenoxydiethylene glycol (meth)acrylate.

[0094] Preferably, the monomers may also be bio-based. Compounds such as IBO(M)A may also be partially bio-based compounds, thereby increasing the bio-based content of the reaction product.

[0095] Preferably, styrene is not used as it is considered a hazardous compound.

[0096] Composition (I) may optionally contain 0-20 wt% of a compound D containing at least one ethylenically unsaturated moiety and different from compounds A, B and C. Compound D is preferably a (meth)acrylate functional compound. Examples of such compounds may vary widely and include, in addition to the radiation curable moiety, various backbone structures such as, but not limited to, polyurethane, epoxy, polyester, polyether or acrylic functional groups. For example, compound D may be selected from polyester (meth)acrylate oligomers, polyurethane (meth)acrylate oligomers, alkoxylated (meth)acrylated oligomers, epoxy (meth)acrylate oligomers, aminated (meth)acrylate oligomers, (meth)acrylated (meth)acrylic oligomers, (meth)acrylic (co)polymer oligomers, or combinations thereof.

[0097] The Tg of composition (I) is at least 90° C. The types and concentrations of the compounds A, B, C and optionally D according to the invention are chosen in such a way that the Tg of composition (I) is at least 90° C.

[0098] In particular, when selecting the Tg of compounds C and / or D, it is important to take into account the Tg of their polymerized form and the concentration of these compounds so that the Tg of composition (I) is at least 90°C. A person skilled in the art is able to select compounds and concentrations so that the Tg of the composition is at least 90°C and maintains good properties, such as a target viscosity. Preferably, the target viscosity is not too high at the temperature at which the composition is applied. Preferably, compound D has a Tg of at least 20°C when homopolymerized, more preferably greater than 30°C, even more preferably greater than 50°C. Compound D may have a lower Tg, but preferably a lower concentration is used in this case.

[0099] In some embodiments, the composition may include a photoinitiator. Curing of the composition may be performed with or without the use of a photoinitiator. Typically, the composition of the present invention includes at least one photoinitiator. Any photoinitiator or mixture thereof that is capable of generating free radicals when exposed to radiation may be used. Preferred photoinitiators include IRGACURE TM 184. Acylphosphine oxide (e.g. IRGACURE TM 819), benzoketals (e.g., IRGACURE TM 651), benzophenones (e.g. available from Allnex BP, IRGACURE available from BASF TM 1173 and IRGACURE TM BP, or Speedcure photoinitiator available from Lambson Ltd.).

[0100] When present, the amount of photoinitiator in the composition of the second aspect is generally 0.01-10 wt%, preferably 0.1-8 wt%, more preferably 0.1-5 wt%, based on the total weight of the composition.

[0101] In other embodiments, the composition includes a free radical generator. Preferably, the content of the free radical generator is 0.01-5wt% of the gross weight of the curable composition (I), preferably 0.1-4wt%, more preferably 0.2-3wt%. Examples of free radical generators are peroxides and azo initiators. Peroxide initiators include diacyl peroxides, hydroperoxides, ketone peroxides, peroxyesters, peroxyketals, dialkyl peroxides, alkyl peresters and percarbonates used alone or together with a redox system. Examples of these peroxides include methyl ethyl ketone peroxide (MEKP), methyl isobutyl ketone peroxide (MIBK), benzoyl peroxide (BPO) and cumene hydroperoxide (CHP). The resin can be cured using a combination of two or more peroxides. Azo initiators include azobisisobutyronitrile (AIBN) and related compounds thereof.

[0102] The composition generally comprises an inhibitor. Examples of suitable inhibitors include, but are not limited to, phenolic inhibitors such as hydroquinone (HQ), methyl hydroquinone (THQ), tert-butyl hydroquinone (TBHQ), p-benzoquinone (BQ), 4-tert-butylcatechol, di-tert-butyl hydroquinone (DTBHQ), hydroquinone monomethyl ether (MEHQ), 2,6-di-tert-butyl-4-methylphenol (BHT), etc. They may also include phosphines such as triphenylphosphine (TPP) and other materials such as trinonylphenylphosphite (TNPP), phenothiazine (PTZ) and triphenylantimony (TPS). When present, the content of the inhibitor is preferably at most 0.5wt% of the composition, particularly 0.0001-0.2wt%, preferably 0.01-0.1wt%.

[0103] Light stabilizers can be classified into UV absorbers (UVA), deactivators (quenchers), hydroperoxide decomposers and free radical scavengers known as hindered amine light stabilizers (HALS).

[0104] In some embodiments, the composition may also include a UV absorber and / or a hindered amine light stabilizer. UVA protects polymers by absorbing damaging UV radiation, while HALS materials protect polymers by reacting with free radicals generated after high-energy UV photons break chemical bonds in the polymer.

[0105] Examples of UVA are benzotriazoles, e.g. 328, 1130, 900, 99-2 and 384-2; Triazines, e.g. 400, 405, 460, 477 and 479; and benzophenones, e.g. 531.

[0106] Examples of HALS include 123. 144 and 292, 2,2,6,6-tetramethylpiperidine and 2,6-di-tert-butylpiperidine.

[0107] When present, light stabilizers may be used in amounts of 0.1 to 5.0 wt %, preferably 0.5 to 2.5 wt %, of the composition.

[0108] The composition may also contain other additives, such as fiber wetting agents, for example functionalized silanes, and (acidic) adhesion promoters.

[0109] In a second aspect, the present invention relates to a composite material comprising the actinic radiation and / or thermally curable composition of the first aspect of the present invention, and a filler material (II).

[0110] In one embodiment, the composite material comprises different amounts of filler material (II), for example, up to 95 wt%, 90 wt%, 80 wt%, 70 wt%, 60 wt% of the total composite material. Suitable filler materials include glass fibers, carbon fibers (including graphite fibers), synthetic polymer fibers (such as polyester fibers, polyaramid fibers, polyamide fibers), inorganic fibers (such as boron fibers), metal fibers (such as steel fibers), carbon nanotubes, mineral nanotubes, etc. Composite materials based on carbon fibers and polyaramid fibers are usually cured by heat.

[0111] In a third aspect, the present invention relates to a method for manufacturing a composite material, comprising the steps of:

[0112] bringing a filler material into contact with the curable composition (I) of the first aspect, and

[0113] • Curing the curable composition (I) in contact with the filler material.

[0114] The composite materials of the present invention can be used for filament winding (with or without a liner), pultrusion, pultrusion, mandrel winding, wet layup or resin transfer molding, vacuum bagging, vacuum infusion, resin infusion, etc.

[0115] The curable composition (I) can also be used to make conductive sleeves, such as glass fiber reinforced conductive printed sleeves. In this case, the radiation curable composition (I) can be contacted with conductive nanoparticles (such as carbon nanotubes) before or during contact with filler material (II).

[0116] The invention is illustrated by the following non-limiting examples. Example

[0117] The following examples illustrate various aspects and embodiments of the present invention.

[0118] Throughout the present invention and particularly in the Examples, the following assays were used.

[0119] Viscosity: Cone and plate viscosity at a given temperature (usually 25°C) and a given spindle speed (also called shear rate).

[0120] Glass transition temperature (Tg) from DMA (ASTM E1640): The glass transition temperature (Tg) was determined using dynamic mechanical thermal analysis (DMTA, instrument DMA800 from TA Instruments) in three-point bending mode. The span between the support points was 20 mm, and small beam-shaped samples of appropriate size (30 mm x 5 mm x 1.6 mm) were provided for analysis.

[0121] The frequency of the oscillatory deformation was 1 Hz and the amplitude was typically 50 μm. The heating rate was 3 °C / min. The glass transition temperature (Tg) was reported as the temperature at which the loss factor reached a maximum (T g =T(tanδ max )).

[0122] Tensile properties: Ultimate elongation. The ultimate elongation was tested according to ASTM D638 using a Zwick Z010 elongation tester equipped with a 500N load cell. Dumbbell-shaped specimens with a thickness of 1.7 mm and a width of 3 mm were used as test specimens. The nominal clamping distance was 30 mm. The test was carried out at a temperature of 23°C and a crosshead speed of 50 mm / min.

[0123] Flexural modulus, strength and strain - Three-point bending test (ASTM D790): Flexural properties were determined by three-point bending tests at 23°C and 30% RH using a universal testing machine Z10 (Zwick) equipped with a 500N load cell. The span between the supports of the bending fixture was 40 mm, and appropriately sized specimens (i.e., 80 mm x 20 mm x 2 mm) were used for testing. The load was applied to the center of the specimen at a steady crosshead speed of 2 mm / min. The ultimate flexural strength and strain at failure were reported.

[0124] Calculation of bending strain εf=6Dd / L 2

[0125] Where, L = support span (mm), d = depth or thickness of the test beam (mm), D = maximum deflection at the center of the beam (mm)

[0126] Hot water / salt water resistance: Glass transition temperature (Tg) and flexural properties were measured after 10 days at 23°C and 30% relative humidity (RH), and after 10 days at 80°C and 28% NaCl solution. The lower the difference (expressed in %), the better the salt water resistance.

[0127] The materials are as follows.

[0128] Table 1: Compounds used to prepare actinic radiation curable compositions

[0129]

[0130]

[0131]

[0132] The results are as follows.

[0133] Table 3: Composition under UV (Ga lamp, 120W / cm, 6000-7000mJ / cm 2 )Performance after curing

[0134]

[0135] Comparative Example Com 1 is an example of WO 2014 / 191308, wherein the composition does not include structural compound A, resulting in a composition having poor ultimate elongation after curing, making the composition unsuitable for many composite material applications.

[0136] Examples Ex 1-6, 9 and 10 are compositions of the present invention, which include compound B containing a cyclic structure, compound A containing a structure and monomer C. They all have high Tg, good to very good ultimate elongation and are very flexible. Compositions with a combination of high Tg and good ultimate elongation are particularly rare.

[0137] Comparative Example Com 5 shows an example described in WO2019104079, in which the composition contains a large amount of monoacrylate EHMA, whose homopolymer has a Tg of less than -10°C. This results in the composition being unsuitable for high heat resistant composite materials because the Tg is only 75°C.

[0138] Results: UV Curing and Brine Analysis

[0139] Table 4: Properties of some compositions after UV curing with and without exposure of samples to 28% NaCl solution at 80°C for 10 days. Both were evaluated after 10 days. X indicates that the sample broke in the fixture before testing.

[0140]

[0141] Table 4 shows that the compositions of the present invention (EX7 and EX8) are able to maintain high Tg, ultimate bending strain and ultimate elongation even after the harsh conditions of exposing the cured compositions to salt water for 10 days at high temperature. Comparative Example Com 4 failed to provide good results due to too low content of structural compound A.

[0142] Comparative Examples Com 2 and Com 3 were diluted with a monomer having 2 or more acrylate groups. This provided a low performance resin composition having a low ultimate elongation and / or ultimate bending strain.

Claims

1. An actinic radiation and / or heat curable composition (I) for composite materials, comprising: (A) at least 20 wt% of a compound A comprising at least 2 ethylenically unsaturated moieties and a moiety selected from the group consisting of polyalkylene glycols, polycaprolactones, polybutadiene or hydrogenated or partially hydrogenated forms thereof, polyisoprene or hydrogenated or partially hydrogenated forms thereof, and / or polyesters derivable from polyols and dicarboxylic acids; (B) at least 20 wt% of a compound B comprising at least 2 ethylenically unsaturated moieties and a cycloaliphatic structure or a heterocycloaliphatic structure; (C) 1 to 40 wt% of a compound C different from compounds A and B, said compound C comprising essentially one ethylenically unsaturated portion and having a viscosity measured at 25° C. of less than 100 mPa.s, preferably less than 50 mPa.s, even more preferably less than 25 mPa.s; and (D) 0-20 wt% of a compound D different from compounds A, B and C, said compound D comprising at least one ethylenically unsaturated moiety; wherein the total content of compounds B and A is 60-99 wt % relative to the total content of compounds A, B, C and optionally D; and Wherein dynamic mechanical analysis is used according to standard test method ASTM E1640, composition (I) has a Tg of at least 90°C after curing.

2. The curable composition (I) according to claim 1, wherein the structural part of compound A is derived from a compound having a Tg below 0°C, preferably below -20°C, more preferably below -30°C, even more preferably below -40°C.

3. The curable composition (I) according to claim 1 or 2, wherein the structural part of compound A is derived from the following polyester: A condensation reaction of a straight-chain aliphatic dicarboxylic acid having 4 to 14 carbon atoms with an aliphatic or alicyclic polyol (preferably an aliphatic diol or an alicyclic diol), Condensation reaction of a dimerized fatty acid compound with an aliphatic or alicyclic diol, or Condensation reaction of dimerized fatty alcohol compounds with aliphatic diacid compounds.

4. The curable composition (I) according to any one of the preceding claims, wherein the structural moiety of the compound A is: The structure is -((CH2) n O) x -or-(CH2CH(CH3)O) x - polyalkylene glycol, wherein n is an integer from 2 to 5, and x is an integer from 5 to 20; The structure is -(C(C=O)(CH2) u O) t - polycaprolactone portion, wherein u is an integer from 3 to 5, and t is an integer from 4 to 20; The structure is -(CH2-CH(CH=CH2) p -(CH2-CH=CH-CH2) q - polybutadiene moiety or a hydrogenated or partially hydrogenated form thereof, wherein the sum of p and q is an integer from 10 to 100, and p≥0 and q≥0; The structure is -(CH2-C(CH3)=CH-CH2) r -polyisoprene moieties, or hydrogenated or partially hydrogenated forms thereof, wherein r is an integer from 10 to 100; or The structure is -O(C=O)-R'-(C=O)OR"-) n - a polyester portion, wherein: R' is a saturated straight chain alkyl group having 2 to 14 carbon atoms, R" is a saturated aliphatic or alicyclic alkyl group, and n is an integer of 3 to 20; R' is a dimerized fatty acid residue, R" is a saturated aliphatic or alicyclic alkyl group, and n is an integer from 3 to 20; or R' is an aliphatic diacid residue, R" is a dimerized fatty diol residue, and n is an integer of 3-20.

5. The curable composition (I) according to any one of the preceding claims, wherein the weight average molecular weight of compound A is 200-10000, more preferably 400-5000.

6. The curable composition (I) according to any one of the preceding claims, wherein compound A is a polyester di- or tri-(meth)acrylate or a polyurethane di- or tri-(meth)acrylate.

7. A curable composition (I) according to any one of the preceding claims, wherein compound B comprises at least 2 ethylenically unsaturated moieties, preferably not more than 8, more preferably not more than 6 ethylenically unsaturated moieties.

8. The curable composition (I) according to any one of the preceding claims, wherein compound B does not contain a structural part of compound A.

9. The curable composition (I) according to any one of the preceding claims, wherein the composition (I) comprises: At least 20 wt% of Compound A, preferably 20-79 wt%, more preferably 20-40 wt% of Compound A; and At least 20 wt% of compound B, preferably 20-79 wt%, more preferably 20-50 wt% of compound B; The total content of compounds B and A is 60-99 wt % relative to the total content of compounds A, B, C and optionally D.

10. Curable composition (I) according to any one of the preceding claims, wherein compound C is added in such an amount that the viscosity measured at 25°C is less than 2500, preferably less than 1800, more preferably less than 1500 mPa.s.

11. A curable composition (I) according to any one of the preceding claims, wherein the composition further comprises 0.01-10 wt%, preferably 0.1-8 wt%, more preferably 0.1-5 wt% of a photoinitiator, relative to the total weight of the composition.

12. The curable composition (I) according to any one of the preceding claims, wherein the composition further comprises 0.01-5 wt%, preferably 0.1-4 wt%, more preferably 0.2-3 wt% of a free radical generator, relative to the total weight of the composition.

13. The curable composition (I) according to any one of the preceding claims, wherein the composition (I) has an ultimate tensile elongation greater than 3% measured according to ASTM D638 and / or an ultimate flexural strain greater than 5% measured according to standard test method ASTM D790.

14. A composite material comprising the curable composition (I) according to any one of claims 1 to 13 and a filler material (II).

15. The composite material according to claim 14, wherein the filler material (II) is glass fiber, carbon fiber, synthetic polymer fiber, inorganic fiber, metal fiber, carbon nanotube or mineral nanotube.

16. A method for preparing a composite material, comprising the steps of: contacting the filler material (II) as claimed in claim 14 or 15 with the curable composition (I) as claimed in any one of claims 1 to 13, and The curable composition (I) in contact with the filler material (II) is cured.

17. Use of the curable composition (I) as claimed in any one of claims 1 to 13 for fiber winding, pultrusion, pultrusion, mandrel winding, wet layup, resin transfer molding, vacuum bagging, vacuum infusion, resin infusion, etc. with or without a liner.

18. Use of the curable composition (I) according to any one of claims 1 to 13 for the manufacture of an electrically conductive sleeve, such as a glass fiber reinforced electrically conductive printed sleeve; wherein the curable composition (I) is contacted with electrically conductive nanoparticles (such as carbon nanotubes) before or during contact with a filler material (II).

Citation Information

Patent Citations

  • Composite composition containing a polycyclic ether polypol

    WO2014191308A1

  • Orthodontic articles comprising polymerized composition comprising at least two free-radical initiators

    WO2019104079A1